Effect Of the Disclosure of Corporate Social Responsibility Practices on The Financial Value of The Companies Listed on The Colombian Stock Exchange - Duque-Grisales, Eduardo; Becerra, Miguel A.; Strobel, Jorge Acosta; Bermudez, Leandro (International Journal of Membrane Science and Technology, 2024)
This research project intends to analyze the financial effects caused by the implementation of Corporate Social Responsibility (CSR) in companies, and the shareholders’ perspective regarding the disclosure of these practices in the stock market. The Colombian Stock Exchange (BVC) market’s reaction was studied, using as a reference 20 companies included in the COLCAP index. The influence of this CSR-type announcements published in important local newspapers was analyzed. The results show that the social practices developed by the Colombian companies listed on the BVC have a positive relationship with financial performance; this fact is evidenced by the change in the share price.